2009
DOI: 10.1080/09603120802527653
|View full text |Cite
|
Sign up to set email alerts
|

Building characteristics associated with moisture related problems in 8,918 Swedish dwellings

Abstract: Moisture problems in buildings have in a number of studies been shown to increase the risk for respiratory symptoms. The study Dampness in Buildings and Health (DBH) was initiated with the aim to identify health relevant exposures related to dampness in buildings. A questionnaire study about home environment with a focus on dampness problems and health was conducted in one county of Sweden (8,918 homes, response rate 79%). Building characteristics that were associated with one or more of the dampness indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 26 publications
(39 reference statements)
6
42
2
Order By: Relevance
“…These results further confirm that condensation on the bedroom window can be an indicator of insufficient ventilation rate in the room. In contrast to the results of Bornehag et al [34] and Hägerhed-Engman et al [33], window condensation over 5 cm was more frequently reported in apartments (32%) than in family houses (15.6%) (Table S2). This is in line with our findings that bedrooms in apartments have lower ventilation rates than in family houses.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…These results further confirm that condensation on the bedroom window can be an indicator of insufficient ventilation rate in the room. In contrast to the results of Bornehag et al [34] and Hägerhed-Engman et al [33], window condensation over 5 cm was more frequently reported in apartments (32%) than in family houses (15.6%) (Table S2). This is in line with our findings that bedrooms in apartments have lower ventilation rates than in family houses.…”
Section: Resultscontrasting
confidence: 69%
“…It is related to relatively low indoor surface temperature of the window and to high indoor air humidity which may be caused by high occupant density or low ventilation rates [3,7,31,32]. In one Swedish study, condensation on windows was mainly associated with older houses, natural ventilation systems (low ventilation rate) and occupancy [33]. In the present study, almost 19% of the inspected homes experienced more than 5 cm of condensation on the window pane in the winter.…”
Section: Resultsmentioning
confidence: 87%
“…It is not clear whether building characteristics can be used as a proxy for these microbial agents. Moisture-related problems in buildings have been interlinked to respiratory problems [24,27,29]. Although the relationship between moisture in homes and microbial exposure is well studied, the relationship between building characteristics is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Moisture has a great influence on fungal growth and bacterial viability [59]. The temperature, ventilation rate and construction details are often reflected in the year of construction which, have been shown to influence the moisture level in dwellings [9,27,45].…”
Section: Introductionmentioning
confidence: 99%
“…The problem is expected to increase with the ongoing climate change leading to more rain in the future in many parts of the world (Andersen et al, 2011;Beggs, 2010;Hägerhed-Engman et al, 2009a). Indoor dampness is related to adverse health effects and/or bad smell and has, for example, been estimated to account for 30-50% of all asthma cases in the United States (Fisk et al, 2007;Hägerhed-Engman et al, 2009b;Mendell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%